Radio‐tomographic images of postmidnight equatorial plasma depletions. Issue 1 (15th January 2014) - Hei, Matthew A.; Bernhardt, Paul A.; Siefring, Carl L.; Wilkens, Matthew R.; Huba, Joseph D.; Krall, Jonathan F.; Valladares, Cesar E.; Heelis, Roderick A.; Hairston, Marc R.; Coley, W. Robin; Chau, Jorge L.; De La Jara, Cesar
Abstract [1] For the first time, equatorial plasma depletions (EPDs) have been imaged in the longitude‐altitude plane using radiotomography. High‐resolution ( 10 km) reconstructions of electron density were derived from total electron content (TEC) measurements provided by a receiver array in Peru. TEC data were obtained from VHF/UHF signals transmitted by the Coherent Electromagnetic Radio Tomography (CERTO) beacon on the C/NOFS satellite. EPDs generated premidnight were observed near dawn. On one night, the bubble densities were highly reduced, 100–1000 km wide, and embedded within a layerlike ionosphere. Three nights later, the EPDs exhibited similar features but were embedded in a locally uplifted ionosphere. The C/NOFS in situ instruments detected a dawn depletion where the reconstruction showed lifted EPDs, implying that the postmidnight electric fields raised sections of ionosphere to altitudes where embedded/reactivated fossil EPDs were detected as dawn depletions. Satellites flying under domelike distortions of the ionosphere may observe these distortions as broad plasma decreases (BPDs).